2016
DOI: 10.18865/ed.26.3.407
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Disparities in African American Compared with European American Women with ER +HER 2- Tumors Treated within an Equal-Access Health Care System

Abstract: <p><strong>Purpose: </strong>Breast cancer mortality rates are higher for African American women (AAW) than for any other ethnic group in the United States. Recent reports suggest that outcome disparities between AAW and European American women (EAW) are present in the ER+HER2- subtype. To improve our understanding, pathological characteristics, mortality and molecular profiles from women treated within an equal-access health care system were evaluated. <strong></strong></p>… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…1e, adj p = 5.8E−04 and adj p = 1.9E−06, respectively; one-way ANOVA with Tukey HSD test). These data correspond with a subset of studies that suggest CRYβB2P1 , and not CRYβB2 , is the gene associated with health disparities and poor outcome in breast cancers [23, 24]. When evaluating the data by first conditioning based on either subtype or race, the same patterns of significance persisted for each gene with only one exception; CRYβB2 expression was no longer significantly higher in Her2 compared to luminal A tumors (Additional file 3: Figure S1A&B).…”
Section: Resultssupporting
confidence: 80%
“…1e, adj p = 5.8E−04 and adj p = 1.9E−06, respectively; one-way ANOVA with Tukey HSD test). These data correspond with a subset of studies that suggest CRYβB2P1 , and not CRYβB2 , is the gene associated with health disparities and poor outcome in breast cancers [23, 24]. When evaluating the data by first conditioning based on either subtype or race, the same patterns of significance persisted for each gene with only one exception; CRYβB2 expression was no longer significantly higher in Her2 compared to luminal A tumors (Additional file 3: Figure S1A&B).…”
Section: Resultssupporting
confidence: 80%
“…Our systematic search clearly indicated that African-American populations, as well as Hispanics, were associated with a risk factor for developing particular forms of BC. ER + BC tends to be associated with Caucasian women, and triple-negative breast cancer tends to be associated with ethnicity/race [ 37 , 38 ]. MiR-34a is more accurate in a large cohort study of tissue-based IBC.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor datasets: Our first dataset (GEO78958, Table S2 , referred to henceforth as dataset #1) had microarray data from 51 AA tumors with luminal (predominantly ER+) breast cancer, and 169 CA tumors 12 . Our second dataset (GSE18229, Table S3 ), referred to henceforth as dataset #2) had microarray gene expression data from 44 AA tumors and 85 CA tumors 25 .…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, our results reflect the DDR landscape of CAs. Since AAs have worse outcomes than CAs 2,12,24 , we hypothesize that resistance to endocrine therapy associated with higher frequency of dysregulation of DDR genes contributes to this outcome disparity. This is an especially relevant hypothesis since DDR pathways are molecular liaisons between external stressors (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation